2018
DOI: 10.1128/iai.00043-18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pig-Tailed Macaque (Macaca nemestrina) as a Model of Human Staphylococcus aureus Nasal Carriage

Abstract: nasal carriage is a common condition affecting both healthy and immunocompromised populations and provides a reservoir for dissemination of potentially infectious strains by casual contact. The factors regulating the onset and duration of nasal colonization are mostly unknown, and a human-relevant animal model is needed. Here, we screened 17 pig-tailed macaques () for carriage, and 14 of 17 animals tested positive in the nose at one or both screening sessions (8 weeks apart), while the other 3 animals were neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Additionally, nasal S. aureus persistence correlated with high baseline levels of MIP-1β, IL-6, and IL-1β, combined with an absence of upregulation of pro-inflammatory cytokines upon inoculation. These findings were confirmed in a similar macaque model for asymptomatic S. aureus carriage [ 75 ]. The effect of pre-existing differences in host immune environment at the time of pathogen acquisition fits with the clinical observation that pre-existing inflammation can predispose the host for carriage or infection with a secondary pathogen.…”
Section: Airway Apcs In Infection and Carriagesupporting
confidence: 63%
“…Additionally, nasal S. aureus persistence correlated with high baseline levels of MIP-1β, IL-6, and IL-1β, combined with an absence of upregulation of pro-inflammatory cytokines upon inoculation. These findings were confirmed in a similar macaque model for asymptomatic S. aureus carriage [ 75 ]. The effect of pre-existing differences in host immune environment at the time of pathogen acquisition fits with the clinical observation that pre-existing inflammation can predispose the host for carriage or infection with a secondary pathogen.…”
Section: Airway Apcs In Infection and Carriagesupporting
confidence: 63%
“…However, due to COVID-19 research, the US is currently facing a shortage of rhesus macaques, suggesting that identification of a suitable alternative macaque species for malaria vaccine studies may be useful. Pigtailed macaques are closely related to rhesus macaques, and are used as models to study numerous infectious diseases, including HIV [ 47 , 48 ], chlamydia [ 49 ], Zika [ 50 ] and Staphylococcus aureus [ 51 ]. Pig-tailed macaques are notably also the natural forest host of P. knowlesi malaria parasites [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that nasal fluids of human S. aureus carriers have less intrinsic anti- S. aureus activity than nasal fluids collected from noncarriers ( 15 , 24 , 25 ) even though the basal components of nasal secretions (e.g., amino acids, salts, organic acids, trace elements, sugars) are not variable between donors ( 26 ). Host antimicrobial peptide polymorphisms fail to distinguish S. aureus carriers from noncarriers, and HNP1 to -3 and various cytokine levels are elevated in carriers, suggesting that these proteins are more the result of SANC than a reason for noncarrier status ( 13 , 15 , 21 , 27 ). Collectively, these insights led us to the current question of how the constantly fluctuating nasal microbiota affect SANC status.…”
Section: Introductionmentioning
confidence: 99%